Exploring the Jastrow Illusion in Humans (Homo sapiens), Rhesus Monkeys (Macaca mulatta), and Capuchin Monkeys (Sapajus apella). (May 2019) - Agrillo, Christian; Beran, Michael J.; Parrish, Audrey E.
In the Jastrow size illusion, two vertically stacked but offset stimuli of identical size are misperceived such that the bottom stimulus is overestimated relative to the top stimulus due to their spatial layout. In this study, we explored whether nonhuman primates perceive this geometric illusion in the same manner as humans. Human adults, rhesus macaques, and capuchin monkeys were presented with a computerized size discrimination task including Jastrow illusion probe trials. Consistent with previous results, humans perceived the illusory stimuli, validating the current experimental approach. Adults selected the bottom figure as larger in illusion trials with identical shapes, and performance was facilitated in trials with a true size difference when the larger figure was positioned at bottom. Monkeys performed very well in trials with a true size difference including difficult discriminations (5% difference in stimuli size), but they did not show evidence of the Jastrow illusion. They were indifferent between top and bottom stimuli in the illusory arrangement, showing no evidence of a human-like (or reversed) bias. These results are considered in light of differences in perceptual processing across primates and in comparison to previous comparative studies of the Jastrow and other size illusions.